2014
DOI: 10.1002/jgm.2760
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 3 (SOCS3) gene transfer prolongs the survival of the murine cardiac allograft by attenuating interleukin-17-producing alloreactive T-cell responses

Abstract: Overexpression of SOCS3 significantly delays cardiac allograft acute rejection, which is associated with reduced allograft proinflammatory leukocyte infiltration and impaired alloreactive IL-17(+) T cell immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…On the other hand, previous sporadic studies have shown that inhibition of STAT1 [ 12 14 ] and STAT4 [ 15 ] using siRNA and knock-out technique alleviates cardiac allograft rejection in a mouse model, suggesting that STAT1/4 plays an important role in cardiac allograft rejection. Although no direct evidence has been established regarding the role of STAT3 in cardiac allograft rejection, several lines of evidence support that STAT3 is involved in cardiac allograft rejection [ 16 , 17 ]. Based on these previous studies, we hypothesized that inhibition of STAT3 would achieve the same effect as STAT3 and STAT4 in cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous sporadic studies have shown that inhibition of STAT1 [ 12 14 ] and STAT4 [ 15 ] using siRNA and knock-out technique alleviates cardiac allograft rejection in a mouse model, suggesting that STAT1/4 plays an important role in cardiac allograft rejection. Although no direct evidence has been established regarding the role of STAT3 in cardiac allograft rejection, several lines of evidence support that STAT3 is involved in cardiac allograft rejection [ 16 , 17 ]. Based on these previous studies, we hypothesized that inhibition of STAT3 would achieve the same effect as STAT3 and STAT4 in cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%